The spider genera Euthycaelus Simon and Schismatothele Karsch (Mygalomorphae, Theraphosidae) - Guadanucci, José Paulo Leite; Weinmann, Dirk (Zootaxa, 2014)
The genus Euthycaelus Simon 1889 is diagnosed based on the examination of type-material and additional material from Venezuela and Colombia. The genus now includes: Euthycaelus colonicus Simon 1889, E. norae sp. nov., E. amandae sp. nov.; Euthycaelus steini Simon 1889 is transferred to Psalistops comb. nov. The genus Schismatothele Karsch 1879 is considered a senior synonym of Hemiercus Simon 1903. Schismatothele includes S. lineata Karsch 1879, S. inflata (Simon 1889) comb. nov., S. modesta (Simon 1889) comb. nov, and S. benedettii Panzera et al. 2011. Hemiercus proximus Mello-Leitão 1923, from Cubatão, São Paulo, Brazil, is transferred to Acanthoscurria proxima (Mello-Leitão 1923) comb. nov. Hemiercus kastoni Caporiacco 1955 is considered a species inquirenda pending the examination of the type material.